1994
DOI: 10.1177/026010609400900404
|View full text |Cite
|
Sign up to set email alerts
|

Homeless & Hungry: The Evidence from Liverpool

Abstract: Much research has established the link between low incomes and poor nutritional standards. A research team from the Centre for Consumer Education & Research at Liverpool John Moores' University recently found that 30% of all families with children in Britain today are spending less on food than what is required to achieve a dietary which adheres, at minimum cost, to the Department of Health's Dietary Recommended Values (DRVs). But very little, if any, research has investigated the nutritional implications of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…Such services have been shown to be crucial in sustaining this population (Rushton & Wheeler, ; Austin et al ., ). However, even with the input of these charities, nutritional inadequacy is a feature of homeless people's diets as found in UK (Rushton & Wheeler, ; Stitt et al ., ; Evans & Dowler, ; Food Standards Agency, ), European (Darmon et al ., ; Malmauret et al ., ; Hickey & Downey, ) and North American (Luder et al ., ; Wolgemuth et al ., ; Austin et al ., ; Silliman et al ., ) studies. All studies report below‐recommended intakes of micronutrients, whereas high intakes of total fat, saturated fat and nonmilk extrinsic sugars (NMES), alongside low intakes of dietary fibre, are also common.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such services have been shown to be crucial in sustaining this population (Rushton & Wheeler, ; Austin et al ., ). However, even with the input of these charities, nutritional inadequacy is a feature of homeless people's diets as found in UK (Rushton & Wheeler, ; Stitt et al ., ; Evans & Dowler, ; Food Standards Agency, ), European (Darmon et al ., ; Malmauret et al ., ; Hickey & Downey, ) and North American (Luder et al ., ; Wolgemuth et al ., ; Austin et al ., ; Silliman et al ., ) studies. All studies report below‐recommended intakes of micronutrients, whereas high intakes of total fat, saturated fat and nonmilk extrinsic sugars (NMES), alongside low intakes of dietary fibre, are also common.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the dietary intake of the homeless population, understanding the factors driving this group's eating habits is crucial. A limited body of literature addresses homeless people's experiences of food insecurity and suggests that multiple and complex factors underpin food consumption; lack of income and access to food storage and preparation facilities stand out as factors governing food choices (Stitt et al ., ; Hickey & Downey, ; Food Standards Agency, ; Wicks et al ., ). Evidence from Australia and the USA suggests that poor dentition, the social aspect of eating and past eating habits additionally impact upon food choices (Wicks et al ., ; Davis et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient analyses in different homeless populations showed a reduced quality of meals 1 and a dramatic shortage in the intake of certain micronutrients (e.g. calcium, magnesium, zinc, iron, vitamin B 2 , vitamin B 6 , vitamin A and folic acid) at concomitantly increased fat intake 2,3 . Physical signs of malnutrition have been frequently observed 1 .…”
mentioning
confidence: 99%
“…This may account for some of the higher levels of fat consumption observed. Stitt et al (1994) reported that homeless people with proper access to a kitchen and storage facilities, also had healthier diets. Another plausible explanation might be the cost of the healthier foods in all locations.…”
Section: P-valuementioning
confidence: 99%